2016
DOI: 10.1016/j.vaccine.2016.08.078
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical identification of vaccine induced protective correlates in human leukocyte antigen expressing transgenic mice infected with Coccidioides posadasii

Abstract: There is an emerging interest to develop human vaccines against medically-important fungal pathogens and a need for a preclinical animal model to assess vaccine efficacies and protective correlates. HLA-DR4 (DRB1*0401 allele) transgenic mice express a human major histocompatibility complex class II (MHC II) receptor in such a way that CD4+ T-cell response is solely restricted by this human molecule. In this study HLA-DR4 transgenic mice were immunized with a live-attenuated vaccine (ΔT) and challenged by the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Mice immunized with one of the four types of yeast cell wall particles or ODN-IFA without rCpa1 served as adjuvant controls. HLA-DR4 transgenic mice are highly susceptible to pulmonary Coccidioides infection (25). Aiming to have surviving mice for comparison of the fungal burden of all vaccinated and control mice at 14 days postchallenge (dpc), we challenged them with a low dose of Coccidioides spores (ϳ30 spores) that would cause a lethal infection around 18 to 20 dpc.…”
Section: Resultsmentioning
confidence: 99%
“…Mice immunized with one of the four types of yeast cell wall particles or ODN-IFA without rCpa1 served as adjuvant controls. HLA-DR4 transgenic mice are highly susceptible to pulmonary Coccidioides infection (25). Aiming to have surviving mice for comparison of the fungal burden of all vaccinated and control mice at 14 days postchallenge (dpc), we challenged them with a low dose of Coccidioides spores (ϳ30 spores) that would cause a lethal infection around 18 to 20 dpc.…”
Section: Resultsmentioning
confidence: 99%
“…conjugated with the adjuvant EP67; a peptide agonist of the biologically active C-terminal region of human complement component C5a (Hung et al, 2012); a multivalent recombinant Coccidioides polypeptide antigen (rCpa1) that consists of three previously identified antigens (Ag2/Pra, Cs-Ag, and Pmp1) and five pathogen-derived peptides with high affinity for human major histocompatibility complex class II (MHC-II) molecules (Hurtgen et al, 2012;Hung et al, 2018;Campuzano et al, 2020); and a rCpa1 encapsulated into glucan-chitin particles (GCP) or b-glucan particles (GP) (Campuzano et al, 2020). Additionally, transgenic mice expressing a human major histocompatibility complex class II (MHC II) receptor have also been employed to study the immune response to coccidioidal vaccines (Hurtgen et al, 2012;Hurtgen et al, 2016;Hung et al, 2018). All the above studies confirmed the protective effect addressed by Th1 and Th17 expansion with higher production of the signature cytokines, IFN-g, and IL-17, respectively.…”
Section: Coccidioidomycosismentioning
confidence: 99%
“…The application of conventional mouse strains to screen for human epitopes and to evaluate vaccine candidates for human use may be problematic, given the differences in the major histocompatibility complex class II (MHC II)–binding properties between murine and human antigen-presenting cells. To bridge the gap, a strain of human leukocyte antigen DR4 type (HLA-DR4; DRB1*0401 allele) transgenic mice, expressing a human MHC II receptor, has been used to evaluate vaccine efficacy and protective immune response against coccidioidomycosis [ 91 , 98 ]. HLA-DR4 mice are able to present peptide antigens of Coccidioides to autologous CD4 + T-cells in such a way that is solely restricted by this human MHC II molecule [ 85 ].…”
Section: Murine Models For Evaluation Of Immune Responses To mentioning
confidence: 99%
“…HLA-DR4 mice are able to present peptide antigens of Coccidioides to autologous CD4 + T-cells in such a way that is solely restricted by this human MHC II molecule [ 85 ]. These results suggest that the HLA-DR4 transgenic mouse strain is one of the practical animal models for preclinical evaluation of the protective efficacy of vaccine candidates, especially subunit vaccines containing human epitopes against Coccidioides infection [ 91 , 98 ]. Human MHC II molecules are highly polymorphic.…”
Section: Murine Models For Evaluation Of Immune Responses To mentioning
confidence: 99%